Comparativo de custos: produção de grãos orgânicos x produção convencional na cidade de Palotina-PR - Gontareck, Fabio Junior (2019)
The present work begins with a preliminary study on organic grain production in western Paraná. The technique of interviews with key informants was used, and 14 informants were interviewed, among technicians and researchers from institutions related to organic production in the western region and some informants from other regions that also work with the theme. Technicians from institutions such as CAPA, GEBANA, EMATER, BIOLABORE and EMBRAPA were interviewed. The questions concerned production systems as well as the profile of organic producers. The results identified the presence of 22 farmers working with certified organic grains, distributed in the municipalities of Palotina, Santa Helena, Diamante do Oeste, Entre Rios do Oeste, Marechal Candido Rondon, Toledo and São Miguel do Iguaçu. Mapped the cities with organic production, the choice was the city of Palotina because of the location and proximity to carry out the research. In the following, the paper presents a comparison of costs of production of organic management vs. conventional management in the city of Palotina PR, in the 2018/2019 crop year, analyzing all aspects of costs involving soy production, its yield potential and positive differential in marketing. The expectation of good prices for organic soybeans on the eve of planting guarantees producers a premium of at least 35% in price compared to conventional soybean, a factor that has encouraged organic producers. The surveyed producers have the prices of their inputs and labor used in the culture, standardized by the market, and therefore have a maximum allowable cost in a product or service, so we analyze in this work based on the target cost, where the cost estimate of an input or service may adjust to the allowable in view of the future selling price.